Diversity of microbial communities in cigar filler leaves with different initial water contents analyzed based on high-throughput sequencing technology - Yumeng Gao; Yumeng Gao; Yihui Wang; Bingqing Hou; Guo Zhang; Chun Jiang; Song Fang; Qian Wang; Yang Ning (Frontiers in Microbiology)
IntroductionTo study the composition and succession of bacterial and fungal communities during the fermentation of cigar filler leaves with varying initial water contents, high-throughput sequencing technology was used to sequence the bacterial 16SrRNA genes and fungal ITS1 genes from cigar tobacco leaf samples. This was followed by analyses of microbial α-diversity, microbial community structure, and bacterial function prediction based on the sequencing data.ResultsThe diversity and richness of microbial communities decreased over time during fermentation under different water content conditions. Among the 18 cigar filler leaf samples, the predominant phyla identified were Proteobacteria, Firmicutes, Actinobacteria, Ascomycota, and Basidiomycota, with the leading genera being Staphylococcus, Sphingomonas, Methylobacterium-Methylorubrum, Pseudomonas, and Humicola. Functional predictions for the bacteria revealed their primary involvement in carbohydrate, lipid, and amino acid metabolism.ConclusionThe initial water content of cigar tobacco leaves influenced the structure and relative abundance of microbial communities during fermentation. While the microbial community exhibited a similar structural composition, there were notable differences in relative abundance. The functional prediction results from PICRUSt indicated that the differences in predicted functional species among samples were minimal, whereas the variations in the abundance of functional species were more pronounced across different fermentation stages and initial water contents.